Obtención de la enzima bromelina de los desechos industriales del procesamiento de ananas comusus, producida en el distrito de poroto. - Abanto Díaz, Angel (2011)
Is evaluated the content of bromelain enzyme in the red and white varieties of pineapple (Ananas comosus) produced in the district of Poroto in 10, 11 and 12 months of development is evaluated. the enzyme activity is also determined, and protein content was estimated specific activity. It is established that operating conditions suitable for maximum precipitation of bromelain using ammonium sulfate saturation at different percentages are: pH 5 to pH 6, temperature range (3 - 5 ° C) time of 10 to 35 minutes. The highest content of Bromelain (0.19%) was obtained in the white variety of 12 months of development.